Challenges of Automated Decisions Brief Report on Hungarian Experiences - Csatlós Erzsébet (BULLETIN OF THE TRANSILVANIA UNIVERSITY OF BRASOV: SERIES VII: SOCIAL SCIENCES LAW, 2024)
Automated decision-making plays a central role in shaping future public services. This paper examines judicial practices at the Administrative Tribunal of Szeged, highlighting challenges in cases involving automated decisions, including limited transparency and barriers to legal recourse. In Hungary, automated systems often function as ‘black boxes’, complicating the appeal process for affected individuals and limiting judicial oversight. This lack of transparency raises significant concerns about the fairness and legality of such decisions, pointing to the need for a robust regulatory framework.